Distinct phenolic, alkaloid and antioxidant profile in betel quids from four regions of Indonesia - Elizabeth Fitriana Sari; Grace Puspita Prayogo; Yit Tao Loo; Pangzhen Zhang; Michael McCullough; Nicola Cirillo (2020)
Abstract Betel quid (BQ) is a chewing mixed package that mainly contains areca nut (AN), betel leaf (Leaf) or betel stem inflorescence (SI), and slaked lime, and is consumed with or without tobacco BQ chewing is common in South East Asia and has been strongly associated with malignant and potentially malignant diseases of the oral cavity. Alkaloids such as arecoline are often accounted for the carcinogenic potential of BQ, however the chemical composition of BQ has not been studied in detail. In the current study, we investigated the total phenolic content (TPC), antioxidant activity (by mean of ferric reducing antioxidant power, FRAP), radical scavenging activity (DPPH test), polyphenolic profile and arecoline content in different components of BQ, namely AN, Leaf or SI, Husk, and blended BQ (BQ mix, containing AN, Leaf or SI and slaked lime). Samples were imported from 4 major regions of Indonesia, namely: Banda Aceh (BA), North Sumatra (NS), West Kalimantan (WK) and West Papua (WP). The highest TPC, FRAP, and DPPH values were detected in AN samples compared to other BQ components, while samples from WP region were of higher values compared to the other regions. High performance liquid chromatography—Mass Spectrometry (LC–MS) analysis showed that Husk contains the widest range of polyphenols, including hydroxybenzoic acids, hydroxycinnamic acids, flavanols, flavonols and stilbenes. Catechin and epicatechin were the main polyphenols detected in BQ, and they were present at the highest concentrations in WP–AN sample. Arecoline was detected in all AN and BQ mix samples and was significantly correlated with catechin and epicatechin, and significantly negatively correlated with p -hydroxybenzoic acid. Notably, arecoline concentration changed significantly when AN was blended in BQ mixtures. The current study is the first to extensively characterise the chemical composition of BQ and provides insight for a better understanding of the interactions of BQ alkaloids and phenolics in the development of oral submucous fibrosis and oral cancer.